Optimizing a Humanistic Approach in Sentencing Drug Offenders in Indonesia - Ramadhany Nasution (Fox Justi : Jurnal Ilmu Hukum, 2025)
Drug abuse in Indonesia continues to increase with a prevalence of 1.73% of the population, while sentencing policies still dominated by imprisonment have caused overcrowding in correctional institutions reaching 187% of capacity. This study aims to analyze the optimization of humanistic approaches in sentencing drug abusers and formulate strategies to strengthen its implementation. The research method used is normative legal research with statutory, conceptual, and case approaches. Legal materials used include primary legal materials consisting of legislation and court decisions, as well as secondary legal materials comprising scientific literature and previous research findings. The results show that the humanistic approach has a normative foundation through the double track system in Law Number 35 of 2009 concerning Narcotics, but its implementation is still constrained by legal structure factors including suboptimal performance of the Integrated Assessment Team, legal substance factors including regulatory inconsistencies, and legal culture factors including the persistence of retributive paradigms. Optimization strategies can be implemented through reconstruction of sentencing policies requiring rehabilitation for abusers, strengthening integrated assessment mechanisms, increasing rehabilitation institution capacity, and transforming law enforcement paradigms toward rehabilitative approaches. This research concludes that optimizing humanistic approaches requires synergy between legal substance reform, institutional strengthening, and legal culture transformation.